Analisis Dampak Pembelajaran Daring Pada Mata Pelajaran Komputer Akuntansi - Hasna Latifah; Muhamad Arief Ramdhany; Yana Setiawan (Jurnal Penelitian Pendidikan, 2022)
The aim of this research was to explore about online learning process and to know the effect of online learning can be seen from the students' comprehension in Accounting Computer subject in vocational high school Cianjur. This research used qualitative descriptive method. Data collection techniques used in this study were interviews and documentation. The types of data used in this study are primary data. Primary data from the result of interview held on the 12 students XII grade Accounting Department in vocational high school Cianjur. The data was analysed by Miles and Huberman technique of analysis, and credibility test data by used member check. From the result of research showed that (1) The implementation of online learning for the Computerized Accounting subject in vocational high schools in Cianjur can be considered inadequate, as seen from students who feel uncomfortable with online learning and the lack of interaction between teachers and students (2) However, students' understanding of online learning for the Computerized Accounting subject in vocational high schools in Cianjur can be considered good, as evidenced by research showing that students can understand the Accounting Computer material by meeting seven indicators of understanding.